Laboratory analysis of ammonium and nitrate concentration of Malalayang Beach Waters - Waropen, Laurina; Tumembouw, Sipriana S (Universitas Sam Ratulangi, 2015)
The purpose of the study was to measure the concentration of ammonium and nitrate of Malalayang Beach Waters. The water was sampling from three sampling stations that were considered to be representative for Malalayang Beach Waters. Methods of sampling techniques, descriptive field survey techniques and sampling locations, were performed at 3 places that were considered to represent the characteristics of Malalayang waters. The results of the Field Work Practice determined that this several sampling methods used sea water is one of Ammonium, point 1 by: 0.745 mg / L, point 2 of: 0.752 mg / L, point 3 of: 0,833 mg / L, while nitrate 1 point for: 4.8 mg / L, point 2 of: 2.7 mg / L, point 3 at: <0.5 mg / L. The conclusion is that the water quality is good for a body of water that is in a situation where the existing parameters in these waters can be maintained and controlled well and remains stable at all times so as to achieve an optimal state as a habitat for fish and for aquaculture. Â Keyword: Sea water, Parameters, Analysis, Ammonium, Nitrate